A CARE-compliant article: Extranasal glial heterotopia in a female infant. Issue 38 (September 2018) - Gan, Weigang; Xiang, Yu; Tang, Yiping; He, Xinrong; Hu, Juanjuan; Yang, Fengjuan; Liu, Shixi; Xian, Junming; Meng, Juan
Abstract: Rationale: Nasal glial heterotopia is a rare type of neoplasm consisting of meningothelial and/or neuroglial elements. Patient concerns: A 17-month-old female infant was evaluated for treatment for a congenital mass present since birth on the right side of the nasal dorsum. Diagnoses: The patient was preoperatively diagnosed with a congenital extranasal neoplasm. Interventions: Surgery was performed under general anesthesia, and the mass was completely resected. The tissue was sent for histological examination, and the diagnosis was of extranasal glial heterotopia. Outcomes: The surgical outcome was good, and no surgical site infection was recorded. After 6 months of follow-up, the girl was asymptomatic with no recurrence. Lessons: Surgical excision, a curative method used to address extranasal glial heterotopia, resulted in no recurrence during the clinical follow-up period. The potential for an intracranial connection must always be kept in mind when considering how to surgically treat a congenital midline mass to prevent the risk of cerebrospinal fluid leakage.